Analysis of Medical Personnel Compliance Factors in Prescribing Based on the National Formulary - Siska Karma Gianti; Agusdini Banun Saptaningsih; Johanes Johanes (Global Management: International Journal of Management Science and Entrepreneurship, 2026)
Medical personnel compliance in prescribing drugs according to the National Formulary (ForNas) is essential to ensure rational therapy, improve service quality, and enhance efficiency in health financing at government health facilities. However, compliance remains a challenge at Johar Baru Regional General Hospital, Central Jakarta. This study aimed to analyze factors influencing medical personnel compliance with ForNas-based prescribing, including drug availability, management policies, and the knowledge, attitudes, norms, and perceptions of medical staff.A qualitative approach was used through in-depth interviews with medical personnel, heads of supporting service sections, and pharmacy unit leaders. The study also involved observation and review of hospital formulary documents, minimum service standards reports for 2024, and monitoring and evaluation reports on prescribing compliance for 2024 and January June 2025. Data were analyzed using thematic analysis supported by NVivo software.The findings indicate that compliance is influenced by medical personnel’s understanding of ForNas policies, clinical experience, and professional attitudes toward prescribing standards. Management factors such as supervision, technological support, and procurement systems also play important roles. Limited drug stocks and suboptimal control systems were identified as major obstacles.The hospital is recommended to strengthen compliance by updating clinical practice guidelines, developing a ForNas-based hospital formulary, improving management support, optimizing information technology systems, ensuring drug availability, and proposing additional ForNas drugs to the Ministry of Health.